On the fence: The impact of education on support for electric fencing to mitigate negative human-baboon interactions in Kommetjie, South Africa - Walsh, Debbie (Department of Biological Sciences, 2022)
There are few studies that empirically test whether education can improve stakeholder support for a particular wildlife management/conservation intervention. Evidence-based decision making is critical for conservation actions, especially when people and wildlife are engaged in negative interactions to the detriment of both. Rising human and baboon numbers in the Cape Peninsula of South Africa is associated with increasing levels of damage to properties, both indirect and direct human-induced injury and mortality to baboons. A possible management intervention to reduce these negative interactions is a baboon-proof electric fence which has already been shown to be very effective in the suburb of Zwaanswyk on the Peninsula but surprisingly has low public acceptance. For this study, I produced a short survey that included an educational video on the welfare, conservation, and lifestyle benefits of a baboon-proof electric fence. Two versions of the same survey were created but with the educational video provided either before or after questions pertaining to the level of support for the fence. Using a randomised controlled trial method, I tested whether the level of support for the fence changed according to the order of viewing the video. I also used a pre- and post-test method to explore whether level of support for the fence changed for those who watched the video at the end and were given a chance to answer the question again about level of support for the fence. The results showed that watching the video before the survey increased the average marginal probability of supporting an electric fence by 15 percentage points and reduced the average marginal probability of not supporting the fence by 17 percentage points. There was also a significant difference in level of support for the fence in the pre- and post-test experiment, and my results show that women were more likely to adjust their response in favour of the fence. Implications of these results are significant as managing a peri-urban species is considerably more effective if there is collaboration, agreement, and support for management measures between and within key stakeholders. This study contributes to the emerging literature on the importance of education in managing human-wildlife conflict.